Factors Related To Occupational Accidents At An Informal Metal Industry - ALAYYANNUR, P. A; NASIRUL HAQI, D.; ERNAWATI, M. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT A large number of employees in the informal sector located in Waru, Sidoarjo, especially in the metal industry sector, has become a target for the Occupational Health Post of Waru. The OHS management system requires a commitment to all elements so that the OHS aspects can be well implemented. The objective of this research was to analyze the relationship between the lack of control and occupational accidents in the metal industry. It was analytical research with a cross-sectional study approach. 75 employees in the informal metal industry were taken as the respondents in this research.RESUMEN Un gran número de empleados en el sector informal ubicado en Waru, Sidoarjo, especialmente en el sector de la industria del metal, se ha convertido en un objetivo para el Puesto de Salud Ocupacional de Waru. El sistema de gestión de OHS requiere un compromiso con todos los elementos para que los aspectos de OHS puedan implementarse bien. El objetivo de esta investigación fue analizar la relación entre la falta de control y el accidente laboral en la industria del metal. Fue una investigación analítica con un enfoque de estudio transversal. 75 empleados en la industria informal del metal fueron tomados como los encuestados en esta investigación.